CORRELATION BETWEEN PLASMA FIBRINOGEN CONCENTRATION AND CLOT WAVEFORM ANALYSIS PARAMETERS AT HOAN MY SAIGON HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the clot waveform analysis (CWA) parameters, including maximum velocity (Min1), maximum acceleration (Min2), and maximum deceleration (Max2), between groups with normal and abnormal fibrinogen concentrations, while APTT and PT remain within normal ranges. In addition, to evaluate the relationship between fibrinogen concentration and CWA parameters.Methods: The study employed a descriptive, cross-sectional, analytical design with a control group, conducted from June to September 2025 at the Laboratory Department of Hoan My Sai Gon Hospital. A total of 631 clinical samples with PT and APTT results within the normal range were included, including 475 samples had normal fibrinogen levels, and 156 samples showed abnormal fibrinogen levels. The PT, APTT, and fibrinogen assays were performed using the CS-2500 automated coagulation analyzer. Data were analyzed using SPSS version 20.Results: In the normal fibrinogen group, the median values of Min1, Min2, and Max2 were 5.05 (4.45-5.73), 0.81 (0.71-0.92), and 0.67 (0.59-0.78), respectively. In the high fibrinogen group, the corresponding values were 7.48 (7.04-8.31), 1.20 (1.13-1.33), and 1,01 (0.95-1.11). Low fibrinogen levels were rarely observed, indicating that elevated fibrinogen was more common. Increasing fibrinogen levels were significantly associated with higher Min1, Min2, and Max2 values (p < 0.001). Spearman’s analysis revealed strong positive correlations between fibrinogen and all CWA parameters (rs > 0.9, p < 0.001), with Min1 showing the strongest correlation (rs = 0.968). Univariate regression confirmed that all three parameters could predict fibrinogen levels, with Min1 providing the best fit (R² = 0.653; lowest RMSE = 1.789).Conclusion: The study demonstrated that an increase in fibrinogen concentration was accompanied by a significant elevation in the Min1, Min2, and Max2 parameters. The clot waveform analysis (CWA) indices showed a strong, positive, and statistically significant correlation with fibrinogen levels. Among the predictive models, Min1 exhibited the highest predictive value for fibrinogen concentration.
Keywords: Clot waveform analysis, fibrinogen.